BUILDING INFORMATION MODELING (BIM) Principles, Usage, Benefits and Challenges for its application in the Kingdom of Saudi Arabia (KSA) - AWAD, IBRAHIM (2017)
This study probes deep into the stratums of the subject of construction management, to potentiate BIM in the light of legal and economic landscape of Kingdom of Saudi Arabia. Previous research and empirical analyses are critically analyzed using descriptive correlations which are then assessed through the utilized primary data in form of survey findings. The study aims at distilling the predicaments presented in the previous research in order to distill the hypothesis and construct the relevant premises for the study. The trends in the literature are extrapolated using both deductive and inductive approaches; which are further cross matched and analyzed to support the presented predicament in this research study. The constructed hypotheses in this chapter are deductively analyzed using descriptive analysis by focusing on both the primary data at hand and the case studies, interpreting the use of BIM in KSA. The collected primary data from the survey questionnaire is analyzed in great detail using exploratory data analysis where different statistical techniques are employed using IBM SPSS statistical software to make important insights and analyze the hypothesis. T-Test is used to test the final hypothesis using SPSS. Case study approach is also used to demonstrate the facts regarding the BIM usage for mega projects and support the predicaments made in the study. The research aims at assisting the KSA’s AEC industry in demystifying the stereo types related to BIM usability and application and construct a case for the potentials and benefits of BIM adaptation for the KSA’s AEC industry. It further demonstrates the advantages of BIM applications and usage over traditional building methods and distills the major challenges and constraints the AEC industry can face in the adaptation of BIM specific to KSA and suggesting important steps for their mitigation.